Empezando con Rafael Alberti (Journal of Parents and Teachers, 2014)
This article takes a look at the life of the poet Rafael Alberti. To do so, it presents his most important stages from a social and literary point of view. In this way, the article exposes in a didactic and clear way the vital development of this author of the 27th century
Keywords: Litterature; Poetry; Didactics; Generation of '27